Cotton in West and Central Africa: From the agricultural revolution to the agro-ecological transition - (:unkn) unknown (My University, 2020)
Since the 1970s, cotton has been a driving force in the transformation of agricultural production systems and a structuring element of local economies in the savannah areas of West and Central Africa (WCA). However, the sustainability of cotton based production systems is often debated because of their effects on soils and the negative impacts of chemical pest control on the environment and human health. Through drastic reforms, the WCA cotton sector overcame the crises, showing its resilience. Today, this sector is facing major challenges on which research must be mobilized: (i) economic (price volatility, producers' income), (ii) social (inclusion of vulnerable groups, role of women and young people, etc.) and (iii) environmental (impact of pesticides, soil degradation, etc.) and linked to climate change. The articles published in this issue present some results and perspectives of research work that can contribute to improve the sustainability of cotton systems in WCA, to open paths towards an agro-ecological transition, and to address the new challenges.
Keywords: African Research